Changes in Educational Wage Premiums in Sweden: 1992-2001 - Magnus Gustavsson (Uppsala University, Department of Economics, 2004)
This paper investigates changes in educational wage differentials in Sweden between 1992 and 2001 and places them in a longer-term perspective. The university wage premium has increased noticeably between 1992 and 2001 while the gymnasium wage premium has been constant. These results, together with previous research for earlier years, suggest that the university wage premium in Sweden has exhibited a clearly positive trend since the early 1980s while the gymnasium wage premium has been constant since the mid 1970s. Unlike the 1980s, relative supply changes do not appear to have been responsible for the rise in the university wage premium over the most recent decade.
Keywords: J31; 330; Returns to skill; Wage structure; Inequality; Bildungsertrag; Schweden